SCHOOLOGY EFFECTS ON STUDENTS’ WRITING ABILITY - Hastomo, Tommy (LPPM STKIP PGRI Bandar Lampung, 2019)
Schoology is a learning management system for students to create, control, and share the content of their learning resources. Also known as teaching media for the virtual learning experience, this course management system provides tools to administer classroom activity for the blended learning activity. The present study was aimed to analyze schoology effects on students’ writing ability, and to investigate the students’ interest towards schoology in the writing process. There were sixty students from the first semester students of English Department at STKIP PGRI Bandar Lampung in 2018/2019 academic years. The samples composed of two groups that consist of the experimental and control group. Schoology was used in the experimental class, and the conventional method was used in the control class. The writing test and questionnaire administered to accomplish the objective of the research. Paired and independent sample t-test was used for analyzing the quantitative data. The findings of the quantitative data revealed the use of schoology was more effective than the use of non-schoology. It was determined by the mean score from both of the groups (82 > 72). The difference (df) of both mean scores was statistically significant based on the t-test value at 0.05 significance level, and the probability value was smaller than the significant level (0.000 < 0.05). In summary, the result of hypothesis testing found that t-value = 5.993 was higher than t-table = 2.000 (p=0.05, df =58). Ha was accepted, and Ho was rejected. In addition, the result of questionnaire analysis confirms that schoology platform was attractive for teaching and learning writing subject.